Uiesh - Quelque part de Joséphine Bacon: desafios de tradução - Silva, Bartira Zanotelli Dias da (2022)
Joséphine Bacon is a leading voice in contemporary French-speaking Canadian Indigenous poetry. Her last book received two important literary awards in 2019. In addition, her life trajectory was recently portrayed in a documentary film awarded at international festivals. In this research, we identified the main characteristics of Bacon's text using performance theories, given that the author considers herself a heir of her people's oral tradition. We also present a reflection on the importance of reading and translating her work for the dissemination and awareness of American indigenous people history and for the appreciation of female voices in contemporary indigenous poetry. This research journey culminates in the proposal for the translation of ten poems from his latest work, Uiesh-Quelque part, followed by analysis of the challenges encountered during the translation process. We selected ten poems in order to illustrate the main themes addressed in Bacon's poetry: age, climate, in-between place, literary creation and hope. We base our poetic translation choices on the studies of De Paula, Berman, Faleiros and Britto.